suppose that (g(x))^2 + 8x = x^2 g(x) + 37

and that g(2) = 7

what is g'(2)

2y*y'+8=2xy+y'*x^2

2*7*y'+8=28+y'*4

y'=2, g'(2)=2

...............................................................................................................................................................................

This answer is correct. Thank you. But how did you get 28 from 2xy?

2xy=2x*g(x)

Since g(2)=7, we know that x=2 and g(2)=y=7

so 2xy=2*2*7=28

o thank you so much!

You are welcome.

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up